Kajian Kecemasan Lansia Di Masa Pandemi Covid 19: Kajian Kecemasan Lansia Di Masa Pandemi Covid-19 - Mestika Lumbantoruan; Asima Sirait; Juneris Aritonang (Yayasan Ahmad Mansyur Nasirah, 2021)
Introduction: The Covid-19 pandemic situation has a direct impact on psycho-social characteristics characterized by anxiety, panic, adjustment disorders, depression, chronic stress and insomnia. Unclear information and uncertainty also cause anxiety for all people, especially in the elderly group. This research was conducted in Tanjung Sari, Batang Kuis, North Sumatra. The Objective: This study aims to examine the anxiety experienced by the elderly group during the covid-19 pandemic. Methods: The design of this study is a descriptive study to examine the anxiety of the elderly group during the covid-19 pandemic. This research was conducted in Tanjung Sari Batang Village, Kuis District, Deli Serdang Regency. The population in this study were all mothers/fathers aged 60-74 years (elderly group) totaling 41 people, using accidental sampling technique. Research tools and materials were used during the research questionnaire research. Results: The results showed that social isolation for the elderly group is considered to be one of the causes of serious mental health problems because of their bio-psycho-social vulnerability. Although social distancing is a key strategy to combat COVID-19, it is a major cause of loneliness, especially in places such as nursing homes or nursing homes, which is a risk factor for depression, anxiety disorders, and suicide in the elderly. The majority of respondents belonged to general anxiety (48%) in dealing with the Covid-19 pandemic in Tanjung Sari Village, Batang Kuis District in 2021. Suggestion: From the results of this study, further research is needed to suppress the anxiety of the elderly group during the Covid-19 pandemic. Pendahuluan: Situasi pandemi Covid-19 ini berdampak langsung terhadap psiko-sosial yang ditandai dengan kecemasan, panik, gangguan penyesuaian, depresi, stres kronis dan insomnia. Ketidak jelasan informasi dan ketidakpastian juga menimbulkan kecemasan bagi seluruh kalangan khususnya pada kelompok lansia. Penelitian ini dilakukan di Tanjung Sari, Batang Kuis, Sumatera Utara. Tujuan: Penelitian ini bertujuan untuk mengkaji kecemasan yang dialami kelompok lansia di masa pandemic covid-19. Metode: Desain penelitian ini adalah penelitian deskriptif untuk mengkaji kecemasan kelompok lansia di masa pandemi covid-19. Penelitian ini dilakukan di Desa Tanjung Sari Batang Kecamatan Kuis Kabupaten Deli Serdang. Populasi dalam penelitian ini adalah seluruh ibu/bapak berusia 60-74 tahun (kelompok lanjut usia/elderly)sejumlah 41 orang, teknik accidental sampling. Alat dan bahan penelitian digunakan pada saat penelitian kuesioner penelitian. Hasil: Hasil penelitian menyebutkan isolasi sosial bagi kelompok lansia dianggap menjadi salah satu pemitu masalah kesehatan mental yang serius karena kerentanan bio-psiko-sosial mereka. Meskipun menjaga jarak merupakan strategi utama untuk memerangi COVID-19, merupakan penyebab utama kesepian, terutama di tempat-tempat seperti panti jompo atau panti jompo yang merupakan faktor risiko depresi, gangguan kecemasan, hingga dan bunuh diri pada kelompok lansia. Mayoritas responden tergolong pada kecemasan umum (48%) dalam menghadapi pandemi Covid-19 di Desa Tanjung Sari Kecamatan Batang Kuis tahun 2021. Saran: Dari hasil penelitian ini diperlukan suatu penelitian selanjutnya untuk menekan kecemasan kelompok lansia pada masa pandemic Covid-19.